English variations in ELT: A case of rural schools in North Kalimantan, Indonesia - Utomo, Aries (Universitas Syiah Kuala, 2023)
American and British English variations in Indonesia are mostly known in society and schools. However, the two variations, including others, have not been taught specifically in schools. This current case study discusses English variations in ELT (English language teaching) by involving two senior high schools in rural areas of North Kalimantan, Indonesia, viewed from students perspectives. There are two aims of conducting this current research, namely: (1) to identify students perceptions of English variations used in learning English at senior high schools and (2) to analyze English variations taught by their English teachers. To collect data, questionnaires, interviews, and document analysis were employed. To analyze data, the interactive analytical model and the statistical formula were employed. Based on the findings, it was found that (1) American English is mostly known among students to speak, and (2) English teachers endorse several kinds of English variations to students. In addition, the teachers still speak mixed English-Indonesian language when explaining materials in the classes. It can be concluded that students in the rural areas of North Kalimantan have been endorsed by several kinds of English variations (mainly American and British English). Yet, the students have not known how to distinguish those variations and when to use them in conversations.